Development of Product Resource Inventory Control Using Forecasting In ‘SMED’ - Wei, Jie Woon; Siti Zubaidah, Ismail (Universiti Malaysia Pahang, 2018)
Industry 4.0 known as “Fourth Industrial Revolution” and also “smart manufacturing” is the current trend of the manufacturing organization. There are four main components for Industry 4.0 which are Internet of Things (IoT), Cyber Physical Systems (CPS), Internet of Services (IoS) and Smart Factory. Product service system (PSS) is a system that combine product and service; to fulfill customer demand and increase their satisfaction level. The main objective of inventory control is to prevent storage overload and ensure storage always have sufficient supply for the customer. By adding sensor, the inventory in storage can be counted and controlled. The output from the sensor can be displayed on the computer and the operator can look out the storage status. Forecasting in inventory can predict the trend of the inventory in future. This allow operator to keep tracking on their reorder point and make sure the inventory never run out.